2018
DOI: 10.1029/2018jd029635
|View full text |Cite
|
Sign up to set email alerts
|

SO2 Observations and Sources in the Western Pacific Tropical Tropopause Region

Abstract: Sulfur dioxide (SO 2 ) is one of the primary source gases for aerosols in the atmosphere. Even at low concentrations, its presence in the upper troposphere and lower stratosphere (UT/LS) provides an important source for aerosol nucleation and growth, and SO 2 has been postulated to be important for the stratospheric sulfur budget. To understand aerosol nucleation and global radiative effects, it is therefore important to quantify how much SO 2 emitted from biogenic and anthropogenic processes at the surface is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…One laboratory study has identified the SO 2 + H 2 O 2 reaction on the surface of ice as a possible sink for SO 2 , although complicating factors, like partial-pressure-dependent reaction prob- abilities and surface poisoning during the reaction, make it difficult to extrapolate the measurements to atmospheric conditions (Clegg and Abbatt, 2001). Furthermore, Rotstayn and Lohmann (2002) found improved model agreement with Arctic sulfate measurements when they included SO 2 oxidation also in ice water. In addition, physical uptake of SO 2 without conversion to S(VI) on ice has been observed in the laboratory (Huthwelker et al, 2001) and may lead to gravitational settling; uptake of SO 2 on ice is not considered in either SOCOL-AERv1 or v2.…”
Section: Observational Disagreements With Socol-aerv2mentioning
confidence: 99%
“…One laboratory study has identified the SO 2 + H 2 O 2 reaction on the surface of ice as a possible sink for SO 2 , although complicating factors, like partial-pressure-dependent reaction prob- abilities and surface poisoning during the reaction, make it difficult to extrapolate the measurements to atmospheric conditions (Clegg and Abbatt, 2001). Furthermore, Rotstayn and Lohmann (2002) found improved model agreement with Arctic sulfate measurements when they included SO 2 oxidation also in ice water. In addition, physical uptake of SO 2 without conversion to S(VI) on ice has been observed in the laboratory (Huthwelker et al, 2001) and may lead to gravitational settling; uptake of SO 2 on ice is not considered in either SOCOL-AERv1 or v2.…”
Section: Observational Disagreements With Socol-aerv2mentioning
confidence: 99%
“…One laboratory study has identified the SO 2 + H 2 O 2 reaction on the surface of ice as a possible sink for SO 2 , although complicating factors, like partial-pressure-dependent reaction prob- (Deshler et al, 2003;Deshler, 2008) abilities and surface poisoning during the reaction, make it difficult to extrapolate the measurements to atmospheric conditions (Clegg and Abbatt, 2001). Furthermore, Rotstayn and Lohmann (2002) found improved model agreement with Arctic sulfate measurements when they included SO 2 oxidation also in ice water. In addition, physical uptake of SO 2 without conversion to S(VI) on ice has been observed in the laboratory (Huthwelker et al, 2001) and may lead to gravitational settling; uptake of SO 2 on ice is not considered in either SOCOL-AERv1 or v2.…”
Section: Observational Disagreements With Socol-aerv2mentioning
confidence: 89%
“…There has been an ongoing debate in the literature regarding the magnitude of the cross-tropopause SO 2 flux and its relative importance in establishing the Junge layer (Rollins et al, 2018). The debate has been fueled by a lack of in situ measurements in the UTLS region, and the high temporal and spatial variability of UTLS SO 2 .…”
Section: Comparison With Utls So 2 Measurementsmentioning
confidence: 99%
“…The debate has been fueled by a lack of in situ measurements in the UTLS region, and the high temporal and spatial variability of UTLS SO 2 . Figure 5 compares the tropical UTLS SO 2 measured by two aircraft campaigns (Rollins et al, 2017(Rollins et al, , 2018 with two annual mean satellite products, MIPAS (Höpfner et al, 2015) and ACE-FTS (Doeringer et al, 2012), averaged during volcanically quiescent periods. The two in situ measurements and the ACE-FTS satellite product all show SO 2 mixing ratios of 5 to 10 pptv around the tropical tropopause (∼17 km).…”
Section: Comparison With Utls So 2 Measurementsmentioning
confidence: 99%